Association study of monoamine oxidase-A gene promoter polymorphism (MAOA-uVNTR) with self-reported anxiety and other psychopathological symptoms in a community sample of early adolescents. (April 2015) - Voltas, Núria; Aparicio, Estefania; Arija, Victoria; Canals, Josefa
Highlights: We have analyzed, by gender, the association of MAOA-uVNTR polymorphism alleles with anxiety subtypes in a sample of adolescents. High-activity variants of the MAOA-uVNTR polymorphism were associated with anxiety symptoms in girls. Low-activity variants of the MAOA-uVNTR polymorphism were associated with social phobia symptoms in boys. Abstract: The polymorphism upstream of the gene for monoamine oxidase A (MAOA-uVNTR) is reported to be an important enzyme involved in human physiology and behavior. With a sample of 228 early-adolescents from a community sample (143 girls) and adjusting for environmental variables, we examined the influence of MAOA-uVNTR alleles on the scores obtained in the Screen for Childhood Anxiety and Related Emotional Disorders and in the Child Symptom Inventory-4 . Our results showed that girls with the high-activity MAOA allele had higher scores for generalized and total anxiety than their low-activity peers, whereas boys with the low-activity allele had higher social phobia scores than boys with the high-activity allele. Results for conduct disorder symptoms did not show a significant relationship between the MAOA alleles and the presence of these symptoms. Our findings support a possible association, depending on gender, between the MAOA-uVNTR polymorphism and psychopathological disorders such as anxiety, which affects high rates of children and adolescents.